An evergreen song model based on P. Ramlee’s songs - Abdul Hamid Adnan,; Syamsul Bahrin Zaibon,; Ahmad Hisham Zainal Abidin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study proposes a model of P.Ramlee’s evergreen songs that involves a basic knowledge on song production model according to a few main aspects, such as basic knowledge about song composition and its five basic concepts, the initial product’s concept based on desired values as well as basic knowledge about album production and recording techniques. The methodology used in this study was through several activities: library search on related P.Ramlee’s history and background, guided inter-view to the key players in the music industry; and the analysis of 32 melodies and 44 lyrics composed by P. Ramlee. The discovery of this study in relation to the novelty of P. Ramlee's evergreen songs reflecting the humanity and social life in community. Through this research, the universal features in a song have highlighted the elements of Malayness. The main finding whch is the proposed model shows that the value of P. Ramlee’s trademarks and thoughts reflect positive and entertainment values, real identity, peace of mind and eventually, all of these attract people to appreciate the song. In practical contribution, the model will be a useful guideline to music composers or producers to compose a qual-ity song that would be an evergreen song.